2017
DOI: 10.1007/s00128-017-2129-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Copper Oxide Nanoparticles on Antioxidant Enzyme Activities and on Tissue Accumulation of Oreochromis niloticus

Abstract: Accumulation of copper oxide nanoparticles (CuO NPs) in gill, liver and muscle tissues of Oreochromis niloticus and its effects on superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) activities in gill and liver tissues were studied after exposing the fish to 20 µg/L Cu over 15 days. Copper levels and enzyme activities in tissues were determined using spectrophotometric (ICP-AES and UV) techniques respectively. No mortality was observed during the experiments. Copper levels increased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Moreover, Nile tilapia can be regarded as a well-established fish model for toxicological studies because of its simple handling, maintenance under laboratory conditions, and prompt response to pollutants and various toxicants [35,36]. Reports showed that the exposure of Nile tilapia to CuONPs caused oxidative stress damage [37,38], histopathological alterations [39], higher accumulation of copper in the liver [40], haemato-biochemical changes [41], and alterations of liver and kidney functions [42].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Nile tilapia can be regarded as a well-established fish model for toxicological studies because of its simple handling, maintenance under laboratory conditions, and prompt response to pollutants and various toxicants [35,36]. Reports showed that the exposure of Nile tilapia to CuONPs caused oxidative stress damage [37,38], histopathological alterations [39], higher accumulation of copper in the liver [40], haemato-biochemical changes [41], and alterations of liver and kidney functions [42].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, depending on different biomarkers has become a valuable tool to track environmental stressors and their effects on aquatic biota (Abdel-Khalek 2015a; Canli et al 2018). Metals may accumulate in fish tissues by direct contact via gills and dermal exposure or by absorption in the digestive tract of fish (Tunçsoy et al 2017). Therefore, the bioaccumulative metal pattern is a relative metal measurement taken by all ways that represent external influences on metal bioavailability (Abdel-Khalek et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…% Inhibition = 100-100 × (GGT with NPs /GGT without NPs). (1) Several studies revealed the effects of copper oxide nanoparticles on tissue accumulation and antioxidant enzymes of Galleria Mellonella L. [30] and Oreochromis niloticus [31]. The previous study of Kojouri et al indicated the beneficial effects of Se NPs on antioxidant activity and weight gain patterns of newborn lambs which may promote lambs' growth rate in the postnatal period [32].…”
Section: Effect Of Cuo and Se Nanoparticles On Gamma-glutamyl Transferase Activitymentioning
confidence: 99%